The triple crisis of Western capitalism : democracy, banking, and currency - Lauk, Tillmann C.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Tillmann C. Lauk discusses law-making at the European level and argues that problems with EU legislation, banking regulation and currency debasement are due to a lack of democratic control. He insists on the need for radical reform both of banking and of international money and makes an important contribution to the debate on the future of finance.
Keywords: Finance -- Law and legislation -- Economic aspects; Law and economics; Global Financial Crisis, 2008-2009.; Law -- European Union countries -- Economic aspects